Review on Performance improvement of Solar PV Panels with alignment of different Environmental Parameters (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the critical environmental parameters that influence photovoltaic performance, including solar irradiance, temperature, wind speed, humidity, and dust deposition, to elucidate the complex links between ambient conditions and panel efficiency Specifically, research indicates that efficiency is directly proportional to solar irradiance and wind speed and is inversely proportional to temperature, humidity, and dew point temperature. To quantify these relationships, linear regression analysis is often employed to model efficiency as a dependent variable against independent meteorological factors, thereby allowing for the prediction of power generation under varying weather scenarios. Field studies have demonstrated that energy losses ranging from 21.4% to 37.5% can occur due to the absence of rainfall over extended periods, highlighting the severity of environmental stressors on photovoltaic systems. Furthermore, specific environmental parameters such as wind velocity, ambient temperature, and dust concentration have been shown to influence power output continuously, with lower humidity levels between 69% and 75% correlating with increased power generation.